Are Anti-Retinal Autoantibodies a Cause or a Consequence of Retinal Degeneration in Autoimmune Retinopathies? - Adamus, Grazyna (Frontiers in Immunology, 2018)
Autoantibodies (AAbs) against various retinal proteins have been associated with vision loss in paraneoplastic and non-paraneoplastic autoimmune retinopathies (AR). There are two major paraneoplastic syndromes associated anti-retinal AAbs, cancer-associated retinopathy (CAR) and melanoma-associated retinopathy (MAR). Some people without a cancer diagnosis may present symptoms of CAR and have anti-retinal AAbs. The etiology and pathogenesis of those entities is not fully understood. In this review, we provide evidence for the role of AAbs in retinal death and degeneration. Studies of epitope mapping for anti-recoverin, anti-enolase, anti-carbonic anhydrase II revealed that although patients’ AAbs may recognize the same retinal protein as normal individuals they bind to different molecular domains, which allows distinguishing between normal and diseased AAbs. Given the great diversity of anti-retinal AAbs, it is likely some antibodies have greater pathogenic potential than others. Pathogenic, but not normal antibodies penetrate the target cell, reach their specific antigen, induce apoptosis and impact retinal pathophysiology. Photoreceptors, dying by apoptosis, induced by other than immunologic mechanisms produce substantial amounts of metabolic debris, which consequently leads to autoimmunization and enhanced permeability of the blood-retinal barrier. Autoantibodies that were made as a part of anti-cancer response are likely to be the cause of retinal degeneration whereas others, generated against released antigens from damaged retina, contribute to the progression of retinopathy. Altogether, AAbs may trigger retinal degeneration and may also exacerbate the degenerative process in response to the release of sequestered antigens and influence disease progression.